Comprehensive fracture tests of concrete for the determination of mechanical fracture parameters. (3rd December 2020) - Lehký, David; Kucharczyková, Barbara; Šimonová, Hana; Daněk, Petr
Abstract: Advanced experimental evaluation of the mechanical fracture properties of quasi‐brittle materials is an important part of the design, assessment, and computational modeling of structures made of these materials. The aim is to determine parameters independent of the test configuration or the size of the test specimens. This paper presents the results of an extensive experimental program which is part of the development of a comprehensive multilevel approach for experimental–computational determination of the mechanical fracture parameters of concrete. Three‐point bending and wedge‐splitting tests were performed simultaneously using three different geometrically similar specimen sizes and two well‐separated depths of initial notches. Before the start of the main testing program, the pilot tests that were performed were aimed at the design of the most appropriate concrete mixture. Special attention was paid to the selection of a maximum aggregate grain size. In order to study the process of concrete aging and the development of its mechanical properties, the accompanying destructive and non‐destructive tests were carried out at different ages of hardening. Fracture parameters were evaluated using the effective crack‐length formulation and work‐of‐fracture method. Finally, the size‐independent specific fracture energy was back‐calculated from the measured specific fracture energy.